Inflammatory Bowel Disease Pharmacist Adherence Counseling Improves Medication Adherence in Crohn's Disease and Ulcerative Colitis. Issue 8 (August 2017) - Tiao, Darren K.; Chan, Webber; Jeganathan, Jayson; Chan, Jenny T.; Perry, Jonathan; Selinger, Christian P.; Leong, Rupert W.
Abstract : Background: While inflammatory bowel diseases (IBD) require long-term medication usage to maintain remission, nonadherence is common and adversely associated with poorer clinical outcomes. Personalized IBD Pharmacist Adherence Counselling, based on the Health Beliefs Model of medication perception, may increase medication adherence. Methods: This prospective multi-center longitudinal parallel study recruited consecutive IBD subjects that were classified as baseline medication non-adherers and adherers. Non-adherers received a single IBD Pharmacist Adherence Counselling intervention at baseline, while adherers served as controls. Medication Adherence Report Scale and Beliefs about Medicines Questionnaire were administered up to 24 months. Medication acceptance was defined as high perception of medication necessity with low concerns. The primary endpoint was medication adherence at 24 months. Results: Of 114 subjects approached, 100 completed follow-up, with 36 being baseline nonadherers (median Medication Adherence Report Scale = 15.0) and 64 baseline adherers (median Medication Adherence Report Scale = 19.0; P < 0.001). At 24 months, nonadherence in the IBD Pharmacist Adherence Counselling group decreased from 100% to 44.4% ( P = 0.001), whereas nonadherence in controls remained unchanged ( P = 0.38). Individually, Beliefs about Medicines Questionnaire Necessity and Concern scores showed no significant changes in both groups, but medication acceptance significantly improved in baseline nonadherers at 12 months ( P = 0.031) with a trend toward durable improvement at 24 months ( P = 0.063). Conclusions: Medication nonadherence in IBD can be improved through a single personalized counseling session by an IBD pharmacist, and the benefit was durable for 2 years. This benefit was through improving the acceptance of medication. Abstract : Article first Published online 17 July 2017.Supplemental Digital Content is Available in the Text.